Epidemiological profile and maternal-fetal transmission of syphilis in pregnant women of Cascavel (PR) - Lago, Ana Carolina de Oliveira; Gomes, Douglas Soltau (Brazilian Journal of Sexually Transmitted Diseases, 2022)
Introduction: Gestational syphilis is a serious public health problem. Diagnosis and treatment failures determine high risk of vertical transmission and may result in adverse perinatal outcomes in a large number of cases. Objective: To analyze the epidemiology of gestational syphilis and its maternal–fetal transmission in Cascavel (PR) to contribute to the improvement of control actions of this disease. Methods: This cross-sectional descriptive study was carried out at the Municipal Department of Health of Cascavel. Socio-demographic information and variables related to the diagnosis and treatment of 135 pregnant women were collected from the database of the Notifiable Diseases Information Systems (SINAN). These women resided in Cascavel and were diagnosed with syphilis, and these were notified from 2008 to 2013. Information on the clinical course of the cases came from notification records of congenital syphilis in the same period. The analysis of the adequacy of treatment received by those pregnant women was based on the recommendations of the Ministry of Health. Results: The incidence of syphilis in pregnant women had risen in the study period and had contributed to a vertical transmission of 23.3% and to the maintenance of the incidence rates of congenital syphilis above the targets set by the Ministry of Health. Although 95.6% of pregnant women have received prenatal care and 99.3% have undergone nontreponemal serology, the treatment prescribed for them was inappropriate in 47.9% of cases. The main reason (82.5%) for this inadequacy was the absence of treatment for the partner. A considerable percentage of missing data in the records of gestational syphilis, and the lack of notification of the mothers of 11 children with congenital syphilis recorded in SINAN in this period were found. Conclusion: An increase in efforts for the notification and improvements in the quality of prenatal care provided to pregnant women, especially to those related to the treatment prescribed for them and their partners, are still needed to ensure control of syphilis among pregnant women and its transmission.